(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
The case definition of AIDS encompasses a spectrum of infections and malignancies, labelled as opportunistic infections. In recent years, numerous studies have outlined the emergence of opportunistic gastrointestinal protozoa that have caused diarrhoeal illness among HIV - AIDS patients. Purpose of present study was to determine the prevalence of opportunistic intestinal protozoal parasites in HIV positive patients with or without diarrhoea. A total of 100 stool samples of HIV positive patients were examined for protozoal parasites by microscopy. Protozoal parasites were detected in 25 HIV positive patients; in 41.37 % of patients with diarrhoea and in 2.38% of patients without diarrhoea. Isospora belli appeared to be a predominant parasite associated with diarrhoea among HIV patients. Cryptosporidium revealed of its asymptomatic carriage along with its association with acute and chronic diarrhoea. Prevalence of Microsporidia and Cyclospora cayetenensis was found to be very low. Key words: HIV; diarrhoea; opportunistic protozoa. DOI: 10.3126/saarctb.v5i1.3079 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(1) 21-24